THE RELATIONSHIP BETWEEN SELF-EFFICACY AND ACADEMIC ACHIEVEMENT - Pratiwi, Lutfi Eka; Laily, Nadhirotul; Sholichah, Ima Fitri (Journal Universitas Muhammadiyah Gresik Engineering, Social Science, and Health International Conference (UMGESHIC), 2021)
This research is motivated by the emergence of the phenomenon of students experiencing a decline in grades. Academic achievement is a skill and ability as an achievement which is considered as a measure of student success. One of the factors that influence academic achievement is self-efficacy. To determine the relationship between self-efficacy and student achievement. Using quantitative research methods with a population of 152 students. Researchers used non-probability sampling technique with incidental sampling technique, obtained 58 samples. Data collection in this study used a scale (questionnaire/questionnaire) via google form using a Likert scale and documentation method in the form of IPS scores (Semester Achievement Index) to measure student achievement. The data analysis technique used Spearman Rho correlation test with SPSS 25.0 program. The results of this study indicate that there is no relationship between self-efficacy and student achievement. This research can be useful as scientific information about the development of educational psychology, especially regarding self-efficacy and academic achievement. The limited number of samples who are willing to become respondents, as a consideration for further researchers to further deepen by using Academic Achievement with different variables.